Sulfur uptake and translocation in maize (Zea mays) grown in a high pH soil treated with elemental sulfur - Karimizarchi, Mehdi; Soltangheisi, Amin; Husin, Aminuddin; Yusop, Mohd Khanif; Othman, Radziah (Taylor and Francis Group, 2018)
A glasshouse experiment was conducted to elucidate the influence of elemental sulfur (S) application rates (0, 0.5, 1.0, and 2.0 g S kg−1 soil) on the release and uptake of S at 0, 20, and 40 days after incubation. Results showed that there was a progressive upward trend in maize leaves, stem, and root S content with application of elemental S. However, maize production followed a nonlinear model. Plants grown in untreated soils suffer from S deficiency and addition of elemental S at a rate of 0.5 g S kg−1 soil alleviated S deficiency. The decrease in maize performance due to the highest S application rate was not related to S toxicity. The greatest leave, stem, and root productions were obtained at S concentrations of 0.41, 0.58, and 0.2%, respectively. Overall, application of elemental S at a rate of 0.5 g S kg−1 soil is recommended for maize performance improvement.